ANALISIS PERTUMBUHAN ENDOGEN: DAMPAK LIBERALISASI PERDAGANGAN DI SEKTOR INDUSTRI MANUFAKTUR INDONESIA, 1979-1997 - Arief, M. Irsan; Sugiyanto, Catur (Journal of Indonesian Economy and Business, 2003)
Trade liberalization in recent years has been part of important world agenda in anattempt to create an unlimited relationship. The endogenous growth literature provides persuasive support that stresses the importance of international trade levels for economic growth. This research uses endogenous growth approach to analyze the effect of international trade on manufacturing industry sector of Indonesia, and importantly to find out the impact in relation to trade liberalization in 1985.The panel data is used and the trade deregulation policy is captured by using dummy variable. A piecewise linear regression model is applied. Observation covers 26 manufacturing sectors between 1979 and 1997.In general, the results show that trade variables used to measure productivity growth rate have small effect on output growth. There is also a positive effect of export growth in one year time lag on productivity but it lesser than that of the imported input growth. We confirm that trade deregulation in 1985 contribute to the increase in productivity of the manufacturing sectors, especially the export oriented firms. Nevertheless, the relatively smaller effect of trade variables than production variables can be a sign of low productivity rate in international trade that is expected to lead the growth of Indonesian manufacturingindustry.Keywords: Trade liberalization, productivity, growth, Indonesian manufacturing industry.